MUHAMMAD THAHIR IBN ‘ÂSYÛR DAN PEMIKIRANNYA TENTANG MAQASID AL-SYARI’AH - Muhtamiroh, Siti (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2013)
In the study of of Islamic law, maqâ?id al-syarî?ah has a central position. It is because the maqâ?id al-syarî?ah does not only imply on the dyamic of Islamic law but also on elasticity of Islam. In discussion on the maqâ?id al-syarî?ah, we can?t forget Ibn ?Âsyûr who has a complete name Muhammad Thahir Ibn ?Âsyûr. He was the continuing pioneer of maqâ?id al-syarî?ah after al-Syathiby. If al-Syathiby was regarded as the founding father of the maqâ?id al-syarî?ah, Ibn ?Âsyûr has developed it into systematized methodology in the Islamic law. Ibn ?Âsyûr said that the ignorance of the significance of the maqâ?id al-syarî?ah in the syari?ah was the leading factor of the fiqh stagnance. Historically, Islam experienced the golden age in the classical periode (750-1250 AD) and it gradually declined in the medieval periode (1250-1800 AD). In the perspective of Islamic law, it was caused by different attention of the maqâ?id al-syarî?ah in the each period.